Diseño e implementación de sistemas domóticos demostrativos - Moreno Sinisterra, Orlando (Universidad Antonio Nariño, 2021)
At present, home automation is an important mechanism, since it allows to easily control a house and buildings, in relation to security, energy saving, air conditioning and water saving. This project seeks to carry out the objective of designing and implementing demonstrative home automation systems composed of sensors and actuators connected to an Arduino board with their designated codes. This will be developed by implementing a light control subsystem through bluetooth commands and the lighting of lamps by means of a pir sensor. With regard to temperature and humidity, information will be captured through sensors, to be displayed through a 16x2 LCD screen